The Dynamics of Vulnerability, Agency and Mental Health Challenges among Students - Baron, Jomarie V (Randwick International of Social Science Journal, 2025)
Students in higher education face challenges stemming from academic, financial, and social stressors, which can have a significant impact on their mental health and well-being. However, the influence of students' vulnerability and agency on mental health has not been fully examined. This study aimed to investigate the relationships between vulnerability, agency, and mental health challenges among students at South Cotabato State College, focusing on academic, financial, and social dimensions. The study employed a descriptive-correlational design, with 280 students selected through stratified random sampling. The Spearman rank correlation coefficient was used to analyze the data. Results indicated a strong positive correlation between vulnerability and mental health challenges, suggesting that higher vulnerability levels are associated with greater mental health struggles. In contrast, agency showed a very weak negative correlation with mental health challenges, indicating that although students exhibited high levels of agency, it did not significantly reduce mental health issues. These findings imply the need for comprehensive support systems that address vulnerabilities, especially in academic, financial, and social contexts, while also considering students' agency in relation to broader environmental factors. It is recommended that educational institutions integrate targeted programs that mitigate vulnerability and support mental health without solely relying on individual attributes. Further research could expand on these findings by examining additional variables influencing student well-being.